Central Density and Low-Mode Perturbation Control of Inertial Confinement Fusion Dynamic-Shell Targets - Trickey , W.; Goncharov , V. N.; Igumenshchev , I. V.; Shvydky , A.; Collins , T. J. B; Campbell , E. M. (Frontiers in Physics, 2021)
The dynamic-shell target is a new class of design for inertial confinement fusion (ICF). These targets address some of the target fabrication challenges prevalent in current ICF targets and take advantage of advances in manufacturing technologies. This study first examines how the dynamic-shell design can be used to control the density of the central region and therefore convergence ratio, thus expanding the design space for ICF. Additionally, the concern of low-mode perturbation growth is considered. A new class of high-performing beam configurations, based on icosahedral polyhedra and charged-particle simulations is proposed. These configurations achieve low levels of irradiation nonuniformity through selection of beam shapes that suppress the dominant symmetrical mode.